2007
DOI: 10.1111/j.1474-9726.2007.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrially encoded cysteine predicts animal lifespan

Abstract: SummaryThe role of genetic factors in the determination of lifespan is undisputed. However, numerous successful efforts to identify individual genetic modulators of longevity have not yielded yet a quantitative measure to estimate the lifespan of a species from scratch, merely based on its genomic constitution. Here, we report on a meta-examination of genome sequences from 248 animal species with known maximum lifespan, including mammals, birds, fish, insects, and helminths. Our analysis reveals that the frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 105 publications
2
86
1
Order By: Relevance
“…In other words, we found that although cysteinyl residues were actively avoided, there were no differences between short-or long-lived species. This observation contrasts with previous results reporting a negative relationship between cysteine usage and longevity, across a wide range of animals covering mammals, birds, reptiles, amphibians, fishes, insects, crustaceans, and arachnids (Moosmann and Behl 2008). Nonetheless, when the correlation analyses were focused on the class Mammalia after correction for the effects of Fig.…”
Section: Resultscontrasting
confidence: 92%
See 2 more Smart Citations
“…In other words, we found that although cysteinyl residues were actively avoided, there were no differences between short-or long-lived species. This observation contrasts with previous results reporting a negative relationship between cysteine usage and longevity, across a wide range of animals covering mammals, birds, reptiles, amphibians, fishes, insects, crustaceans, and arachnids (Moosmann and Behl 2008). Nonetheless, when the correlation analyses were focused on the class Mammalia after correction for the effects of Fig.…”
Section: Resultscontrasting
confidence: 92%
“…and methionine are particularly sensitive to oxidation (Berlett and Stadtman 1997). Interestingly, mitochondrially encoded cysteine and methionine have both been correlated negatively with longevity (Moosmann and Behl 2008;Aledo et al 2011). Even though both cysteine and methionine are negatively related to longevity, it may be that cysteine is a pro-oxidant while methionine is an anti-oxidant, as we have previously argued (Aledo et al 2011).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…There is little evidence for greater antioxidant enzyme capacity in longer-lived species (reviewed in Perez et al 2009b; also see Page et al 2010a). Protein oxidative damage could also be prevented in longer-lived species by the systematic evolutionary replacement of cysteine residues with amino acids less susceptible to oxidative modification (as Moosmann and Behl (2008) demonstrated for mitochondrial DNA-encoded proteins); however, there is no evidence that this has occurred in nuclear DNA-encoded proteins that function either in the mitochondria or cytosol (Moosmann and Behl 2008). Similarly, proteins of naked mole rats actually have higher cysteine content than shorter-lived mice (Perez et al 2009a).…”
Section: Discussionmentioning
confidence: 99%
“…One suggestion, however, is that long-lived mammals and birds may have adapted to an increased lifespan by evolving macromolecular components more resistant to oxidative damages (Pamplona & Barja 2007;Min & Hickey 2008;Moosmann & Behl 2008). This conclusion points to a new hypothesis potentially explaining the variations of mtDNA substitution rate across species-longevity-dependent selection.…”
Section: The Longevity Hypothesismentioning
confidence: 99%